2017
DOI: 10.1186/s13102-017-0072-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between logbook-reported and objectively-assessed physical activity and sedentary time in breast cancer patients: an agreement study

Abstract: BackgroundIncreasing physical activity (PA) and decreasing sedentary time (ST) have important health effects among breast cancer patients, a growing population group. PA and sedentary behaviors are complex multi-dimensional behaviors and are challenging to monitor accurately. To date few studies have compared self-reports and objective measurement in assessing PA and ST in women undergoing breast cancer treatments. The aim of the present study was to compare self-reports and objective measures for assessing da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…Our findings add to the preliminary evidence indicating self-reported physical activity can be substantially inflated as compared to device-based measurement among breast cancer survivors ( 12 , 14 , 15 ). The discrepancy between self-report and accelerometer measures in the current study was striking; median self-reported MVPA at 6 and 18 months was more than triple accelerometer-measured MVPA.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Our findings add to the preliminary evidence indicating self-reported physical activity can be substantially inflated as compared to device-based measurement among breast cancer survivors ( 12 , 14 , 15 ). The discrepancy between self-report and accelerometer measures in the current study was striking; median self-reported MVPA at 6 and 18 months was more than triple accelerometer-measured MVPA.…”
Section: Discussionsupporting
confidence: 64%
“…Thus, it is possible that participants’ reports of their typical physical activity over the past month might not directly align with their actual physical activity the following week. Future research should examine agreement among accelerometer and self-report measures for the same week ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because self-reported physical activity differs from objectively measured physical activity among BCS [48] this review only includes studies that utilized objective measures of physical activity (i.e., accelerometers) rather than self-reported data, Table 3. Six studies were included [40][41][42][43]49,50]; of these, two assessed physical activity longitudinally [40,42], four compared physical activity to controls without previous cancer [41,43,49,50], and one study reported physical activity longitudinally and in comparison to controls [40].…”
Section: Energy Expenditure In Breast Cancer Survivorsmentioning
confidence: 99%
“…PA was assessed at the end of the exercise intervention (6 months after randomisation) and at 12-month follow-up (12 months after the end of the exercise intervention), using previously validated instruments: a tri-axial PA monitor, the SenseWear Armband mini (SWA) [ 28 , 29 ] and a 7-day PA diary [ 30 ]. At each measurement point, participants were asked to wear the SWA 24 h a day for seven consecutive days and fill out the diary during the same period.…”
Section: Methodsmentioning
confidence: 99%